Perubahan komunikasi pemustakayang termediasi oleh komputer - Endang Fatmawati (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2015)
User now use the computer while the media access to information. One aspect that emerged from the development of new media is a meeting between user in the area of virtual communication. This is called the computer mediated communication and represented by text. The presence of cyber media to form a new way of communicating, because the process through which the message are distributed via the internet. Changes in library communication is Zuckerberg time. Transformation can strengthen the role of libraries.